2022
DOI: 10.1186/s40035-022-00285-2
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 mutant knock-in mouse models: therapeutic relevance in Parkinson's disease

Abstract: Mutations in the leucine-rich repeat kinase 2 gene (LRRK2) are one of the most frequent genetic causes of both familial and sporadic Parkinson’s disease (PD). Mounting evidence has demonstrated pathological similarities between LRRK2-associated PD (LRRK2-PD) and sporadic PD, suggesting that LRRK2 is a potential disease modulator and a therapeutic target in PD. LRRK2 mutant knock-in (KI) mouse models display subtle alterations in pathological aspects that mirror early-stage PD, including increased susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 204 publications
(276 reference statements)
0
11
0
Order By: Relevance
“…Despite the near complete protection against neurotoxicity in our experimental systems here, LRRK2-mediated effects cannot explain every pathological endpoint associated with environmental toxicants implicated in PD risk 65,66 . For example, we found that a threshold exists for LRRK2 protection against mitochondrial toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the near complete protection against neurotoxicity in our experimental systems here, LRRK2-mediated effects cannot explain every pathological endpoint associated with environmental toxicants implicated in PD risk 65,66 . For example, we found that a threshold exists for LRRK2 protection against mitochondrial toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…In other PD mouse models, including single knock-out (e.g. DJ-1, PINK1, PRKN), triple PINK1/PRKN/DJ-1 knock-out or LRKK2-R1441G transgenic mice, no dopaminergic neurodegeneration was observed albeit their motor coordination is altered [63][64][65][66]. Herein, we showed that physiological levels of Miro1 with p.R285Q mutation led to behavior impairments and SNpc TH loss in an age-dependent way.…”
Section: Discussionmentioning
confidence: 70%
“…Future studies investigating how phosphorylated and unphosphorylated states of EZRIN control astrocyte morphogenesis through modulation of the cytoskeleton will be helpful in deciphering mechanisms of astrocyte morphogenesis. LRRK2 G2019S ki/ki mice do not recapitulate cardinal motor symptoms of PD because there is no detectable dopaminergic neuron loss in these mice [67][68][69] . LRRK2 mutation carriers show non-motor symptoms in comparison to non-carriers, such as hyposmia and decreased cognitive performance 150 41,151,152 .…”
Section: Lrrk2 G2019s Mutation Disrupts Excitatory and Inhibitory Syn...mentioning
confidence: 98%
“…PD patients with the LRRK2 G2019S mutation also have non-motor symptoms, such as depression, hallucinations, and sleep and cognitive disorders 43,57,66 . Several rodent models with LRRK2 G2019S mutation have been generated; however, these models do not show motor dysfunction or dopaminergic neuron loss [67][68][69] . However, non-motor symptoms such as cognitive dysfunction is common in PD, indicating impairments in numerous brain regions, including the cerebellar cortex 70,71 .…”
Section: Astrocytic Lrrk2 Controls Astrocyte Morphology Through Erm P...mentioning
confidence: 99%